Potential roles of melatonin and ABA on apple dwarfing in semi-arid area of Xinjiang China - Tianci Yan; Chuang Mei; Handong Song; Dongqian Shan; Yanzhao Sun; Zehui Hu; Lin Wang; Tong Zhang; Jixun Wang; Jin Kong (PeerJ, 2022)
Dwarfing is a typic breeding trait for mechanical strengthening and relatively high yield in modern apple orchards. Clarification of the mechanisms associated with dwarfing is important for use of molecular technology to breed apple. Herein, we identified four dwarfing apple germplasms in semi-arid area of Xinjiang, China. The internodal distance of these four germplasms were significantly shorter than non-dwarfing control. Their high melatonin (MT) contents are negatively associated with their malondialdehyde (MDA) levels and oxidative damage. In addition, among the detected hormones including auxin (IAA), gibberellin (GA), brassinolide (BR), zeatin-riboside (ZR), and abscisic acid (ABA), only ABA and ZR levels were in good correlation with the dwarfing phenotype. The qPCR results showed that the expression of melatonin synthetic enzyme genes MdASMT1 and MdSNAT5, ABA synthetic enzyme gene MdAAO3 and degradative gene MdCYP707A, ZR synthetic enzyme gene MdIPT5 all correlated well with the enhanced levels of MT, ABA and the reduced level of of ZR in the dwarfing germplasms. Furthermore, the significantly higher expression of ABA marker genes (MdRD22 and MdRD29) and the lower expression of ZR marker genes (MdRR1 and MdRR2) in all the four dwarf germplasms were consistent with the ABA and ZR levels. Considering the yearly long-term drought occurring in Xinjiang, China, it seems that dwarfing with high contents of MT and ABA may be a good strategy for these germplasms to survive against drought stress. This trait of dwarfing may also benefit apple production and breeding in this semi-arid area.